Strategi Pengelolaan Pasar Simpang Tiga Kec. Luhak Nan Duo Kab. Pasaman Barat - Safria Anita; Gusril Basir (Universitas 45 Surabaya, 2023)
Traditional markets are markets built and managed by the government, private sector, cooperatives or non-governmental organizations with business premises in the form of kiosks, shops, tents and the like. A traditional market is a market that is not only a place for transactions between sellers and buyers, but the market has become a means of driving the wheels of the economy on a large scale. But in its management, there are still many problems that occur in terms of facilities, infrastructure and cleanliness. The purpose of this research is to find out how the traditional market management strategy of Simpang Tiga, Luhak Nan Duo sub-district, West Pasaman district is based on an Islamic economic perspective. This type of research is a qualitative descriptive method with data collection carried out through observation, interviews, documentation. The data analysis technique was carried out by SWOT analysis. The results of this study are in the form of strategies based on SWOT analysis data processing, namely: making good use of market spatial planning, building and repairing and maintaining facilities and infrastructure, improving access to market roads, cooperating with the government, and developing special procedures for waste management.